Épocas de aplicação de nitrogênio para híbridos de mamona no sistema plantio direto em safrinha - Moro, Edemar; Costa Crusciol, Carlos Alexandre; Teixeira de Carvalho, Larissa Lozano [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
The castor bean cultivation has a high demand for nitrogen, in addition, the efficiency of nitrogen fertilization in most cases is low, so that this essential nutrient is provided at the appropriate time. The objective was to study the time nitrogen application in castor bean hybrids under no-till system in off-season. The experiment was carried out in an experimental area located in Botucatu, São Paulo State, Brazil, for two growing off-seasons (2006 and 2007). The experimental design was a randomized block in split plot design, with four replications. The plots were constituted by two castor bean hybrids (Lyra/Savana in 2006 and Lyra/Sara in 2007). Six combination of times out rates (0-0, 0-100, 100-0, 30-70, 70-30, 50-50 kg ha-1 of N) side dressing nitrogen fertilization constituted the subplots. The N source used was ammonium nitrate, applied 20 days after emergence and 40 days after emergence. Measurements were carried out: dry matter production of shoots, nitrate and ammonium leaf, leaf analysis, yield components and nitrogen factor utilization. The highest grain yield was obtained to the hybrid Lyra with nitrogen fertilization. In 2006 the highest nitrogen utilization factor to the hybrid Lyra was obtained with the form 70-30 and in the 2007 with 50-50.
Times of nitrogen fertilization for castor bean hybrids under no-till system in off-season
Keywords: Ricinus comunnis L; Nitrogen fertilization and yield components